(untitled) (Sociología y Tecnociencia, 2012)
A large majority of Governments are trying to achieve the development and acceptance of its projects of e-Government as a way to improve the perceived quality of the services it provides and to facilitate access to them. Once developed various models that explain the adoption of e-Government, is stated the need to study this phenomenon jointly with the digital divide. In this line, this work analyses the moderator role played by the educational level of citizens in the adoption of e-Government, concluding that the educational level moderates the relationship between the effort expectancy and social influence and use intention. To the contrary arises that the educational level of the citizen doesn ́t moderate the relationship between the performance expectancy and use intention, neither the one that linked to this last and facilitating conditions with the use of e-Government platforms.